Parenting, Peer Relationships, Academic Self-efficacy, and Academic Achievement: Direct and Mediating Effects - Llorca, Anna; Cristina Richaud, María; Malonda, Elisabeth (Frontiers in Psychology, 2017)
The aim of the present study is to analyze the relation between authoritative and permissive parenting styles with the kinds of adolescent peer relationships (attachment, victimization or aggression), and of the latter ones, in turn, with academic self-efficacy, and academic performance, in three waves that range from the early-mid adolescence to late adolescence. Five hundred Spanish adolescents, of both sexes, participated in a three-wave longitudinal study in Valencia, Spain. In the first wave, adolescents were either in the third year of secondary school or the fourth year of secondary school. The mean age in the first wave was 14.70 (SD = 0.68; range = 13–16 years). Child Report of Parental Behavior Inventory (Schaefer, 1965; Samper et al., 2006), Peer Attachment (from the Inventory of Parent and Peer Attachment by Armsden & Greenberg, 1987), Victimization (from the Kit at School, Buhs et al., 2010), Physical and Verbal Aggression Scale (Caprara & Pastorelli, 1993; Del Barrio et al., 2001), items of academic self-efficacy and items of academic performance were administered. Structural equations modelling – path analysis was employed to explore the proposed models. The results indicated that parenting styles relate to the way the adolescents develops attachments to their peers and to academic self-efficacy. The mother’s permissive style is an important positive predictor of aggressive behavior and a negative predictor of attachment to their peers. At the end, peer relations and academic self-efficacy are mediator variables between parenting styles and academic performance.